Designing Online Courses for Screen Reader Users - Kearns, Lorna R.; Frey, Barbara A.; McMorland, Gabriel (Online Learning, 2013)
A review of multiple online courses at one institution was conducted by a skilled screen reader user for the purpose of assessing the extent to which the courses were navigable and understandable to online students using assistive technologies. This paper identifies features of online courses that may present problems for screen reader users and recommends solutions to address those problems. The following two overarching recommendations are suggested and elaborated: 1) Just as a roadmap assists drivers in navigating unfamiliar terrain, principles of clarity, consistency, and organization should be applied to the design of online courses to orient students to the virtual learning environment. 2) Web pages and course documents should make effective use of metadata, i.e., machine-understandable information about computer-based content, in order for course material to be accurately understood by students using a screen reader.